High-performing photoanodes with a cost-effective n-InGaN/p-Cu2O heterostructure for water splitting. (5th February 2023) - Huang, Pengda; Hu, Dong; Zhao, Qingjiang; Li, Tianbao; Xu, Bingshe
Abstract: InGaN nanorods are highly desirable candidates for photoelectrochemical water splitting photoelectrodes because of their inherent material properties. However, their use is hindered by their low carrier separation efficiency and high production cost. Therefore, in this work, InGaN nanorods were grown by a low-cost HCVD method, and, p-n heterojunction n-InGaN/p-Cu2 O photoanodes were successfully constructed by electrodeposition to address the low carrier separation efficiency. The optimized InGaN/Cu2 O photoelectrodes with uniform morphology have a maximum photocurrent density of 4.2 mA cm −2 at 1.23 V vs. RHE, which is 8.4 times that of pure InGaN nanorod photoelectrodes. A comprehensive experimental study showed that this approach of constructing p-n heterojunctions greatly enhances the carrier separation efficiency and alleviates the charge transfer kinetic bottleneck at photoelectrodes. Graphical abstract: Image 1 Highlights: InGaN nanorods with 65% In content using halide chemical vapor deposition (HCVD). Electrodeposition process was used to grow p-type Cu2 O in situ on n-InGaN nanorods. Current density of the InGaN/Cu2 O photoelectrode at 1.23 V vs. RHE was 4.2 mA cm −2 . Maximum current density in InGaN-based photoelectrodes prepared by HCVD so far.